REPRESENTASI ANAK DALAM FILM GARAPAN SINEAS LOKAL KOTA PALU: Analisis Semiotika Pada Film Halaman Belakang dan Film Gula & Pasir - Roman Rezki Utama; Stepanus Bo'do; Geraldy Yohanes Kurniawan Lumanauw (Kinesik, 2023)
This study aims to determine representation the figure of a child in Halaman Belakang film and Gula & Pasir film. The research method is descriptive qualitative by using Charles Sanders Peirce's semiotic analysis. Based on the results of this study, it shows that in Halaman Belakang film and Gula & Pasir film, there are findings of signs of representation of children who are constrained, representations of children who do not care about their parents, representations of children who express their emotions, representations of children who are not polite, representations of children who do not respect parents, and representations of children who respect parents based on the representament, object, and interpretant. The similarities and differences between the two films show the figure of a child who does not care about and does not respect his parents, and a child who cares for and respects his parents. The general representation of child characters in both films describes themselves as the main character in the film, both of which take the point of view of a child.